2008
DOI: 10.1109/tbme.2008.919126
|View full text |Cite
|
Sign up to set email alerts
|

AnIn VitroModel of a Retinal Prosthesis

Abstract: Epiretinal prostheses are being developed to bypass a degenerated photoreceptor layer and excite surviving ganglion and inner retinal cells. We used custom microfabricated multielectrode arrays with 200-μm-diameter stimulating electrodes and 10-μm-diameter recording electrodes to stimulate and record neural responses in isolated tiger salamander retina. Pharmacological agents were used to isolate direct excitation of ganglion cells from excitation of other inner retinal cells. Strength-duration data suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 52 publications
(62 reference statements)
11
96
0
1
Order By: Relevance
“…RGC responses to repetitive stimulation pulses have been reported for normal retinas (Fried et al, 2006;Sekirnjak et al, 2006;Jensen and Rizzo, 2007;Ahuja et al, 2008). However, few reports have described RGC responses of degenerated retinas evoked by repetitive pulse stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…RGC responses to repetitive stimulation pulses have been reported for normal retinas (Fried et al, 2006;Sekirnjak et al, 2006;Jensen and Rizzo, 2007;Ahuja et al, 2008). However, few reports have described RGC responses of degenerated retinas evoked by repetitive pulse stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal properties of light-elicited patterns can vary considerably across types, suggesting that the prosthetic must be able to create a similarly wide range of temporal responses, including high-frequency bursts of spiking used by some cell types. Previous studies that have explored the temporal responsiveness of retinal ganglion cells have shown that a single, short-duration (ϳ0.1 ms) stimulus pulse elicits a single action potential that is phase-locked to the onset of the cathodal pulse (Ahuja et al 2008;Fried et al 2006;Sekirnjak et al 2006). In this manner, trains of short-duration pulses have been shown to elicit trains of action potentials.…”
mentioning
confidence: 97%
“…Differential equations that describe and solve the problem are presented. Electric field behavior produced by electrical stimulation of the tissue is stated using the Maxwell equations and its derivatives [6][7][8][9][10][11]. Electric field is calculated by solving the Maxwell equations under quasi-static conditions…”
Section: Three-dimensional Retina Stimulation Modelmentioning
confidence: 99%